The Application of the Problem-Based Learning Model to Improve Learning Outcomes in Islamic Education and Character Building - Syafii, Muhammad (Jurnal Keprofesian Guru Keagamaan, 2025)
This study investigates the application of the Problem-Based Learning (PBL) model to improve students’ learning outcomes in Islamic Education and Character at SDN 005 Cemaga Selatan. The research was motivated by low student engagement and achievement resulting from traditional, teacher-centered methods. PBL, as a student-centered approach, emphasizes active participation, collaboration, and critical thinking through real-world problem-solving. The study employed a Classroom Action Research (CAR) design conducted in two cycles, each involving planning, implementation, observation, and reflection. Data were collected using observation sheets, learning outcome tests, and field notes, and analyzed both qualitatively and quantitatively. The findings indicate a significant improvement in students’ learning achievement and participation: the average score increased from 69.0 in the pre-cycle to 73.0 in Cycle I and 87.0 in Cycle II, with the mastery level improving from 60% to 100%. The results show that PBL not only enhances cognitive achievement but also fosters moral reasoning and reflective learning aligned with Islamic values. The study concludes that implementing PBL in Islamic Education contributes to meaningful learning experiences and moral development. Recommendations are provided for teachers and schools to integrate PBL principles into daily teaching practices to support holistic student growth.